Bronchoscopic Management of Central Airway Obstruction in Children after Heart Surgery - Ayten, Omer; Özdemir, Cengiz; Dalar, Levent; Karaci, Ali Riza (The Thoracic and Cardiovascular Surgeon, 2025)
Central airway stenosis following congenital heart malformation surgery is a rare but significant cause of postoperative weaning failure. In selected cases, bronchoscopic interventions are effective treatment options for managing these kind of airway obstructions and achieving successful weaning.The data of six pediatric patients who were unable to be weaned from mechanical ventilation due to central airway obstruction following congenital heart malformation surgery were retrospectively analyzed. Rigid and flexible bronchoscopies were performed under general anesthesia for six patients.Six patients (4 males and 2 females; age range: 4 months to 6 years) with an airway obstruction after surgery due to congenital heart malformations included the study. Three patients had an obstruction of the left main bronchus, two of the right main bronchus, and one of bilateral main bronchus. Balloon dilatation was applied to one patient, mechanical dilatation was applied to three patients, and airway stent was applied to two patients. Two of six patients died from nonprocedural causes (acute respiratory distress syndrome due to pneumonia and cardiac arrest due to severe heart failure) and four patients were weaned successfully from mechanical ventilation and they were still alive during the follow-up period. No procedural-related mortality was seen in the study population. In one patient, stent placement could not be performed due to desaturation and hemodynamic instability during the procedure, and in another patient, granulation tissue developed due to a covered metallic stent, and the metallic stent was removed and replaced with a biodegradable stent.In selected cases, bronchoscopic interventions offer efficient approach to managing airway obstructions due to congenital heart malformation surgery.
Keywords: airway (includes related subject matter); congenital heart disease; CHD; pediatric; bronchial disease (includes injury, stenosis, tumor, etc.)